Pemanfaatan Biji Kedawung (Parkia timoriana) Sebagai Produk Pangan Fungsional Desa Curahnongko, Jember - (Indonesia), Haddaf Abror; (Indonesia), Camelia Firdausy; (Indoensia), M. Ghifari Abdllah; (indoensia), Dian Agung Pangaribowo; (Indonesia), Muhammad Iqbal (Fakultas Pertanian_Universitas Tidar, 2024)
The use of kedawung seed (Parkia timoriana) in Curahnongko Village, Tempurejo District, Jember Regency, is relatively low due to a lack of available foods containing kedawung seed. One possible option is to include kedawung seed as an ingredient in desserts like brownies. The program to use kedawung seeds as functional food is carried out in four stages: a) development of the TOGA Conservation Group; b) socialization; c) traditional socialization and demonstration program; and d) monitoring and evaluation. This program has improved TOGA Conservation Group's understanding, skill, and ability to use kedawung seed as an extra ingredient in brownies.